2015
DOI: 10.1073/pnas.1523410113
|View full text |Cite
|
Sign up to set email alerts
|

Genetically targeted single-channel optical recording reveals multiple Orai1 gating states and oscillations in calcium influx

Abstract: Orai1 comprises the pore-forming subunit of the Ca2+ release-activated Ca2+ (CRAC) channel. When bound and activated by stromal interacting molecule 1 (STIM1), an endoplasmic reticulum (ER)-resident calcium sensor, Orai1 channels possess high selectivity for calcium but extremely small conductance that has precluded direct recording of single-channel currents. We have developed an approach to visualize Orai1 activity by fusing Orai1 to fluorescent, genetically encoded calcium indicators (GECIs). The GECI–Orai1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 44 publications
4
61
0
Order By: Relevance
“…Another group successfully detected nanodomain Ca 2þ signals in the surrounding region of Ca V 2.2, a voltage-dependent Ca 2þ channel, by fusion with a FRET-typed GECI, TN-XL (66). A single-FP-typed GECI, G-GECO, was also used by attaching it to Orai1, a Ca 2þ release-activated Ca 2þ channel on the plasma membrane, and results from studies with G-GECO revealed that Ca 2þ influx through Orai1 makes several characteristic patterns, such as rapid transients and periodic oscillation (67).…”
Section: Subplasmamembranementioning
confidence: 99%
“…Another group successfully detected nanodomain Ca 2þ signals in the surrounding region of Ca V 2.2, a voltage-dependent Ca 2þ channel, by fusion with a FRET-typed GECI, TN-XL (66). A single-FP-typed GECI, G-GECO, was also used by attaching it to Orai1, a Ca 2þ release-activated Ca 2þ channel on the plasma membrane, and results from studies with G-GECO revealed that Ca 2þ influx through Orai1 makes several characteristic patterns, such as rapid transients and periodic oscillation (67).…”
Section: Subplasmamembranementioning
confidence: 99%
“…Recently developed alternative methods, such as detecting the gating conformational change with Tb 3+ or other fluorescent probes (Gudlur et al 2014) or recording optically from single Orai1 channels tagged with genetically encoded calcium indicators (Dynes et al 2016), may offer a way around these limitations.…”
Section: 7 Channel Gatingmentioning
confidence: 99%
“…Recently, Dynes et al . () generated a ORAI1‐GECO construct and thereby were able to measure optical single‐channel recordings of ORAI1 in a TIRF microscope set‐up. Furthermore, using a TPC2‐GECO construct (TPC‐GCaMP6), Ambrosio et al .…”
Section: Introductionmentioning
confidence: 99%